Hsp90 Flexibility and Development of its Inhibitors for the Treatment of Cancer - Gupta, Sayan D. (Current Chemical Biology, 2018)
Hsp90 is a molecular chaperone which is engaged in the repair of diverse oncogenic proteins. Additionally, it is overexpressed in cancer cells along with co-chaperones, whereas normal cell Hsp90 (less than 2 % of cellular proteins) resides in an uncomplexed state. Hence, this chaperone is an encouraging target for the discovery of novel chemical entities against cancer. Proteins execute their functions by interacting with various macromolecules. The conformational flexibility of polypeptides helps them to adopt a shape corresponding to their partner molecules. Hsp90 is a highly flexible polypeptide which can accommodate a wide variety of dynamic states. The major cause for this structural dynamism is the intrinsic flexibility of the protein. In this review, the structure and function of Hsp90 chaperone are discussed. This is followed by a description of the factors regulating the proteins flexibility. Finally, dynamics dependent drug designing strategy (induce fit docking and molecular dynamics simulation) for the discovery of novel Hsp90 inhibitors is discussed.
Keywords: induced fit docking